The mechanical power output in water polo: a case report - Gatta, G.; Fantozzi, S.; Cortesi, M.; Patti, F.; Bonifazi, M. (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: The coaches use normal swimming parameters as reference to develop the plan training activities even if the water polo player does not move as a swimmer in the best hydrodynamic position. The purpose of this work is to compare the mechanical power required to play a game as computed with a new model based on the specific analysis of the swimming`s technique of water polo. METHODS: Two indices of passive drag were measured with the method of towing at different speeds (1.2-1.4-1.6-1.8-2 m/s) in a water polo player (27 years, 1.77 m, 79 kg). The first index was obtained in the position of "best glide" (Swim), the second index was obtained in a "head-up" position of the subject (Wp). The active drag in the two conditions was estimated (Kjendlie, 2008) as 1.5 times the value of passive drag. To calculate the drag in acceleration, the maximum acceleration reached by the typical water polo starting in "trudgeon" was measured. Then, that value (m/s*s) was reproduced in the tow Ben-Hur by measuring the drag value in the specific condition. The value of the mechanical power required to the water polo was computed multiplying the drag by speed: Power-drag = k*vn*v. The data of game model is obtained from a video analysis of the individual distances and velocity on a international water polo match in World Championship 1994. The total swimming time was defined for four steps of velocity and the values of mechanical power were calculated for all steps. RESULTS: The average mechanical power of a water polo game in Swim model was 150489J/2400s=62.70W, in WP model is 481375J/2400s=200.57W. DISCUSSION: The crawl technique used by water polo players involves a higher energy cost compared to the crawl technique used in swimming due to the need to keep the head out of the water. The players perform a series of swimming sprints with starts from standstill alternated to stationary phases. The mechanical power required to the water polo players could be more than three-fold higher than that required for freestyle swimming at the same velocities. Our study highlights the importance of developing specific training programs for water polo, addressing the higher requirements of mechanical power, taking into account the specific movement techniques and comparing the distances travelled using different swimming techniques.